Mixed norm Bergman-Morrey-type spaces on the unit disc - Samko, Stefan (2017)
We introduce and study the mixed-norm Bergman-Morrey space A (q;p,lambda) , mixednorm Bergman-Morrey space of local type A (loc) (q;p,lambda) , and mixed-norm Bergman-Morrey space of complementary type (C) A (q;p,lambda) on the unit disk D in the complex plane C. Themixed norm Lebesgue-Morrey space L (q;p,lambda) is defined by the requirement that the sequence of Morrey L (p,lambda)(I)-norms of the Fourier coefficients of a function f belongs to l (q) (I = (0, 1)). Then, A (q;p,lambda) is defined as the subspace of analytic functions in L (q;p,lambda) . Two other spaces A q;p,lambda loc and (C) A (q;p,lambda) are defined similarly by using the local Morrey L (loc) (p,lambda) (I)-norm and the complementary Morrey (C) L (p,lambda)(I)-norm respectively. The introduced spaces inherit features of both Bergman and Morrey spaces and, therefore, we call them Bergman-Morrey-type spaces. We prove the boundedness of the Bergman projection and reveal some facts on equivalent description of these spaces.